Profile of Students’ Problem Solving Skills and the Implementation of Assisted Guided Inquiry Model in Senior High School - Muslimah Cindikia; Hainur Rasyid Achmadi; Binar Kurnia Prahani; Saiyidah Mahtari (Indonesia Approach Education, 2020)
The purpose of this research to analyze profile students’ problem solving skill and the implementation of assisted guided inquiry at senior high school. The type of research is used the preliminary research method with data collection techniques such as tests and questionnaires. The data are obtained, analyzed descriptively qualitatively. The results of this study show that only a few students can work on the material using problem-solving strategies (A-Assessing the problem (identifying principles to be used in problem-solving), C-create a drawing (translating words in the form of pictures containing about problem-solving instructions), C-conceptualize strategy (outlining the steps that will be used in solving the problem), E-executing the solution (applying the formula to solve the problem by the steps) and finally S-scrutinize the result (giving a level of confidence and give a reason) in solving dynamic electricity problems. Totally of the students, five students had low problem-solving skills, and 25 students who had moderate problem-solving skills. Totally of the students, five students had low problem-solving skills, and 25 students who had moderate problem-solving skills. The lowest problem-solving strategy value is at point S (scrutinize the result). Implementation of learning models provided is not ideal so that it causes students to be less active so that problem-solving skills are lacking and no laboratory supports the learning process. Students are not introduced to the existence of a virtual laboratory (PhET) as a laboratory replacement. So to improve students' problem-solving skills required appropriate learning methods.